Tourist destination image and consumer behaviour: The case of the Azores - Melo, Helena Maria Pascoal; Moniz, Ana Isabel; Silva, Francisco José Ferreira; Batista, Maria da Graça (Journal of Tourism, Sustainability and Well-being, 2017)
Destinations are currently seeking to become more distinctive in an increasingly competitive market in which image is a decisive element in tourists’ destination selection. This study sought to understand the Azores’ overall image as a tourist destination in major source markets and to ascertain these markets’ level of satisfaction and behavioural intentions concerning the archipelago. The literature review in this paper addresses the definition of tourist destination image and the issue of satisfaction, since these influence intention to return and/or intention to recommend tourist destinations. The results indicate that (1) overall image influences satisfaction and intention to recommend and/or return to tourist destinations and (2) satisfaction influences intention to recommend and/or return to tourist destinations. This study also verified that most tourists are very satisfied with the Azores, as well as having a quite positive overall image of this destination.